Kolaborasi Internasional dalam Pengabdian Masyarakat: English Camp untuk Meningkatkan Keterampilan Calon Karyawan Indonesia dalam komunikasi Global - Darmawan, Agus; Siti Aminah; Intan Maulida Qorry’ Aina (LP3M IAIFA Kediri, 2025)
This article discusses the implementation of English Camp as a community service program aimed at improving the English skills of job seekers in Wonosalam, Jombang, East Java through international collaboration. The objective is to assess English Camp's efficacy in enhancing participants' English proficiency, confidence, and readiness for the global job market. This article is presented using a qualitative research, utilizing a case study framework. Data collection was conducted through participatory observation, detailed interviews, and the review of relevant documentation. The results showed significant improvements in participants' speaking, listening, and writing skills, along with increased confidence in communicating with native speakers. Participants also reported satisfaction with the program's interactive and supportive learning environment. The program not only improved language skills but also equipped participants with essential soft skills for the workplace. Future research should explore long-term impacts and consider expanding the program to include more participants and diverse learning contexts.